Phenotype Standardization of Angioedema in the Head and Neck Region Caused by Agents Acting on the Angiotensin System. Issue 4 (24th June 2014) - Wadelius, M; Marshall, S E; Islander, G; Nordang, L; Karawajczyk, M; Yue, Q‐Y; Terreehorst, I; Baranova, E V; Hugosson, S; Sköldefors, K; Pirmohamed, M; Maitland‐van der Zee, A‐H; et al.
<x xml:space="preserve">Abstract</x> Angioedema is a potentially life‐threatening adverse reaction to angiotensin‐converting enzyme inhibitors and angiotensin receptor blockers. To study the genetic etiology of this rare adverse event, international consortia and multicenter recruitment of patients are needed. To reduce patient heterogeneity, we have standardized the phenotype. In brief, it comprises swelling in the head and neck region that first occurs during treatment. It should not coincide with urticaria or have another likely cause such as hereditary angioedema. Clinical Pharmacology & Therapeutics (2014); 96 4, 477–481. doi:10.1038/clpt.2014.138